The Impact of Social Norms on Cohesion and (De)Polarization - Miranda J. Lubbers; Marcin Bukowski; Oliver Christ; Eva Jaspers; Maarten van Zalk (Social Inclusion)
In recent years, political and social polarization has increased across many societies, evolving from mere issue‐based disagreements into affective polarization, in which citizens dislike and distrust members of opposing groups. This trend undermines social cohesion and the effective functioning of democratic institutions. Despite extensive interdisciplinary research into polarization, the role of social norms—shared expectations about typical and appropriate behavior—in mitigating such divisions remains underexamined. This thematic issue seeks to address this gap by investigating how social norms shape intergroup dynamics in polarized contexts. To frame the contributions, this introductory article first outlines the concepts of polarization and social norms and then briefly reviews the literature on the role of norms in polarization and depolarization. Subsequently, we introduce the contributions included in this thematic issue, which explore four central themes: (a) the role of social norms in fostering tolerance and depolarization; (b) the association between norm deviations and non‐normative behaviors and political polarization; (c) the negotiation versus contestation of social norms by competing groups; and (d) the influence of social networks on intergroup attitudes and behaviors that can facilitate depolarization processes. We conclude with reflections on future research directions.